Madrasah Head Strategic In Improving The Performance of Madrasah Aliyah Teachers In Tangerang District - Mukhtar, Muallim; Saefurridjal, Achmad; Sauri, Saupyan; Iriantara, Yosal (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2023)
The purpose of this study was to find out the strategic management activities carried out in internal and external environme at Madrasah, obstacles encountered, and solutions to overcome problems. The research method uses a qualitative approach that describes the findings at the research location. Data collection techniques through interviews with school principals, curriculum representatives, teachers, and students. Field observation to find phenomena that occur. Documentation studies in the form of official records, books, photos of school activities. Research results show that: (1). Strategic planning in improving the performance teachers, has been implemented in the form of guidelines, which compile all aspects that follow the functions to be carried out, according to the priority scale that will be carried out, namely identifying problems in improving teacher performance. (2). The organizing strategy has been carried out in the form of establishing delegation and management functions, although not all aspects and functions of organizing have been carried out properly, namely the division of labor has not been based on the competence possessed by the teacher. (3). The implementation strategy has been carried out in the form of implementing programs that have been planned to improve the performance teachers, but there are still important aspects in the implementation which are still annual routines that tend to be administrative (4). Strategic Evaluation has been carried out in the form of a strategic management oversight function. (5). Obstacles encountered are the supervisor and teacher factors, educational facilities, and budget / for financing, which are the main obstacle factors in implementing.